2002
DOI: 10.1046/j.1365-2486.2002.00546.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nutrition and soil warming on stemwood production in a boreal Norway spruce stand

Abstract: The boreal forest is expected to experience the greatest warming of all forest biomes. The extent of the boreal forest, the large amount of carbon contained in the soil, and the expected climate warming, make the boreal forest a key biome to understand and represent correctly in global carbon models. It has been suggested that an increase in temperature could stimulate the release of CO2 caused by an increased decomposition rate, more than biomass production, which could convert current carbon sinks into carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
144
2
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 147 publications
(161 citation statements)
references
References 38 publications
14
144
2
1
Order By: Relevance
“…In addition, soil moisture has been reported as a major factor affecting soil N mineralization, which influences the N availability, along a temperature gradient in four European shrubland ecosystems (Beier et al 2008). This mechanism was unlikely to be significant in our study area, where soil moisture was relatively similar among all treatments (Strömgren and Linder 2002). In boreal forest ecosystems, growth of soil microorganisms was found to primarily be controlled by C rather than N availability (Ekblad and Nordgren 2002).…”
Section: Responses Of Aob and Aoa Abundance To Soil Warming And Fertimentioning
confidence: 85%
See 2 more Smart Citations
“…In addition, soil moisture has been reported as a major factor affecting soil N mineralization, which influences the N availability, along a temperature gradient in four European shrubland ecosystems (Beier et al 2008). This mechanism was unlikely to be significant in our study area, where soil moisture was relatively similar among all treatments (Strömgren and Linder 2002). In boreal forest ecosystems, growth of soil microorganisms was found to primarily be controlled by C rather than N availability (Ekblad and Nordgren 2002).…”
Section: Responses Of Aob and Aoa Abundance To Soil Warming And Fertimentioning
confidence: 85%
“…In late autumn, when soil temperature on the control plots approached 0°C, the soil temperature of warmed plots was reduced by 1°C per week until they were the same as unheated control plots. Detailed descriptions of design and performance of the soilwarming system are found in and Strömgren and Linder (2002).…”
Section: Soil Warming and Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…At the ecosystem level, several studies have observed a decrease in soil respiration in association with metabolic down-regulation at warmer temperatures (Luo et al 2001;Stromgren and Linder 2002;Giardina and Ryan 2000;Misson et al 2007). However a number of studies have attributed this apparent acclimation to other factors; as temperature increases the imbalance arises between the supply (photosynthesis) and the utilization (respiration) of the most labile C fraction, product of plant activity (Rustad et al 2001;Kirschbaum 1995Kirschbaum , 2004Gu et al 2004;Eliasson et al 2005;Hartley et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Change in soil freeze-thaw cycles as a result of alterations in energy flow could have large effects on hydrological and biogeochemical processes (Euskirchen et al 2007) and must be accounted for to constrain uncertainty in biogeochemical modeling of future conditions. Warmer soil temperature could have positive impacts on boreal forest productivity (Strömgren and Linder 2002) as well as plant community and soil composition (Charles and Dukes 2009;Pumpanen et al 2012;Thakur et al 2014). However, adverse effects of changes in soil temperature have also been reported on below-ground processes including decreased soil aggregate stability (Oztas and Fayetorbay 2003), increased nutrient leaching ), higher root mortality , greater rates of soil organic matter mineralization (Davidson and Janssens 2006), hydrological flow path alteration, increased soil microbial respiration, and cell wall lysis ) among others.…”
Section: Introductionmentioning
confidence: 99%